Penambahan Bubuk Ekstrak Ikan Haruan (Channa Striata) terhadap Kekuatan Tekan dan Perubahan Warna Glass Ionomer Cement (GIC) Tipe II Secara In Vitro - Yudistira, Muhammad Wisnu; Alhawaris, Alhawaris; Sulistiani, Dewi Arsih; Masyhudi, Masyhudi; Yani, Sinar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to prove the effect of adding haruan fish extract powder (Channa striata) on increasing the strength of type II Glass Ionomer Cement (GIC) filling materials. The method used is a laboratory experimental method with a post-test-only control group design approach. There are 6 treatment groups, namely the addition of 10mg, 20mg, 30mg, 40mg, 50mg, and without addition (pure). This research was conducted at the Dental Materials Laboratory, Faculty of Medicine, Dentistry Study Program, Mulawarman University and PT. Sucofindo Samarinda. The study was conducted from August 2022 to March 2023. The results showed that the greatest compressive strength of glass ionomer cement (GIC) was found in pure glass ionomer cement (GIC) without the addition of haruan fish extract which showed a compressive strength value of 37.0 MPa. The more amount of haruan fish extract powder added, the lower the strength of the glass ionomer cement will be. There is a difference in compressive strength between pure glass ionomer cement (GIC) without haruan fish extract powder and glass ionomer cement (GIC) with haruan fish extract. In conclusion, Glass Ionomer Cement (GIC) type II without the addition of fish extract powder must have the greatest compressive strength compared to the addition of 10 mg, 20 mg, 30 mg, 40 mg, and 50 mg. The addition of haruan fish extract powder decreased the strength of the glass ionomer cement and no color change occurred. Keywords: Haruan Fish Extract Powder, Glass Ionomer Cement, Compressive Strength